Stratégies interactives d’évaluation formative selon différentes formes scolaires : les classes régulières, de maternelle et d’éducation physique - Joëlle Morrissette; Grégoire Compaoré (Recherches en Éducation)
As in many OECD countries, Quebec opted for a curriculum revision based on a competency approach since 2001. One of the main problems stemming from this approach is the operationalization of the competency assessment for teachers. In the context of this article, we expose and discuss the interactive formative assessment strategies (non-instrumented) of preschool and primary school teachers mobilized as part of this approach. These strategies are examined with respect to the various “school forms” (Vincent, 1980) that characterize the work environment of teachers. The analysis conducted identifies strategies common to the three school forms and outlines more specifically unique characteristics, namely the prevalence of a normative perspective in a regular class, of accountability in a physical education class and of differentiation in a kindergarten class. In this respect, some contexts seem to be more favourable for formative competency assessment.